Advances in the neuroimaging of panic disorder. (29th August 2013) - Pannekoek, Justine Nienke; van der Werff, Steven J.A.; Stein, Dan J.; van der Wee, Nic J.A.
Abstract : Models of the neuroanatomy of panic disorder (PD) have relied on both animal work on fear and on clinical data from neuroimaging. Early work hypothesised a network of brain regions involved in fear processing (e.g. the amygdala), but more recent work has also pointed to the involvement of other cortical areas and other brain circuitry (e.g. the insula and anterior cingulate cortex). Studies investigating functional and structural brain connectivity in PD may ultimately shed light on the extent to which the neuroanatomy of PD is localised versus distributed, and on how current treatments alter this neuroanatomy. Copyright © 2013 John Wiley & Sons, Ltd.